Implementation Of Digital Marketing as An Effort to Increase Sales for MSMEs In the City of Bandar Lampung in The New Normal - SAEPUDIN, Saepudin; AZKA, Fuad; YUNIFER, Muhammad Glenn (PT. Keberlanjutan Strategis Indonesia, 2023)
Purpose:Since the World Health Organization (WHO implemented the Coronavirus as a global pandemic, with case data in Indonesia as of June 29, 2020, with the number of confirmed cases reaching 55,092 people, it had a major impact on various sectors, one of which is the economic sector, especially MSME businesses. This study aims to see the role of digital marketing in increasing MSME sales in Bandar Lampung City during the COVID-19 pandemic.Methodology:This study uses a qualitative method called literature study, namely the technique of collecting data and information through various literature or references. The primary references used in scientific writing are scientific journals, information, and national and international news. The data used are secondary data, which are mostly obtained from websites and government statistics that are relevant to the object being studied. Processing of the data and information contained in this scientific paper using the descriptive methodFindings:In this scientific paper, digital marketing strategies will be explained with the concepts of social media marketing and content marketing. Digital marketing provides several benefits, including connecting sellers and buyers on the internet, expanding market share, and generating higher sales.Implication:By implementing digital marketing as a marketing strategy, sales turnover for MSME players will increase.